(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study aimed to assess the in vitro and in vivo antitick efficacy of commonly used acaricides in order to suggest efficient acaricides to livestock owners was conducted in South Omo Zone, Southern Ethiopia. According to Drummond’s method, the Adult Immersion Test (AIT) was applied to assess oviposition inhibition of engorged female ticks. Also, in vivo efficacy field trial of Deltamethrin 1% pour-on, Amitraz 12.5%, and Ivermectin 1% injection was conducted on a goat kept under a pastoral production system in the study area. A total of 528 fully engorged female R. decoloratus and R. pulchellus ticks were tested through the adult immersion test (AIT). A statistically significant (p<0.05) mean percent oviposition control was achieved by two in vitro tested acaricides. Amitraz induced 67.30±7.33 (min= 58.07%; max=74.02%) mean percent oviposition control while, Deltamethrin achieved 100±00 (min=100%; max=100%) on ticks from bovine. Similar results were obtained on ticks from caprine using Amitraz and Deltamethrin, and mean percent oviposition control was 82.90±2.7 (min=79.04%; max=85.01%) and 100±00 (min=100%; max=100%), respectively. A 61.45% and 73.15% oviposition control of R. decoloratus and R. pulchellus from bovine, and 81.77% and 84.03% oviposition control of R. decoloratus and R. pulchellus from caprine, respectively, were observed in in vitro studies. However, Deltamethrin was able to completely prevent oviposition in both bovine and caprine tick species. At the recommended field concentration, Amitraz, Ivermectin, and Deltamethrin, achieved 97.22%, 85.29%, and 99.03% effectiveness, respectively, in eliminating adult ticks from infested goats. We suggest both Amitraz and Deltamethrin were effective against Ixodid ticks infesting ruminants in the research area when used in the recommended dosages; however, more confirmatory in vivo field data is required. Int. J. Agril. Res. Innov. Tech. 15(1): 1-10, June 2025